BUDAYA ORGANISASI DENGAN EMPLOYEE ENGAGEMENT PADA KARYAWAN CREDIT UNION (CU) PANCUR SOLIDARITAS KABUPATEN KETAPANG, KALIMANTAN BARAT - Stepany Dwitiantiny; Sutarto Wijono (Direktorat Riset dan Pengabdian Masyarakat Universitas Bina Darma Palembang, 2021)
Employee engagement is an important factor in the company. This is because employee engagement can ensure the company's long-term growth and make the company profitable in an increasingly challenging business environment. In this study, the researcher wanted to examine organizational culture with employee engagement, for Pancur Solidaritas Credit Union (CU) employees. This study is a quantitative research, in this study using two measuring tools, namely: Organizational culture scale by Fey and Denison (2003) with a total of 36 items and UWES (Utrecht Work Engagement Scale) proposed by Schaufeli and Bakker (2003) with a total of 17 items. The study involved 65 employees of Pancur Solidaritas Credit Union (CU). Based on the results of the Pearson correlation calculation, the correlation coefficient (r) between organizational culture variables and employee engagement is 0.706 with a significance value of 0.000 (p <0.05), from these results indicate that there is a positive and significant relationship between organizational culture and employee engagement. . The higher the organizational culture, the higher the employee engagement will be. The organizational culture of Pancur Solidaritas Credit Union (CU) employees is in the “very good” category and employee engagement of Pancur Solidaritas Credit Union (CU) employees is in the “high” category. The results of the assessment are based on the results of the